On the Understanding of the Role of Continuous Experimentation in Technology-Based Startup - Bernardes, Matheus; Marczak, Sabrina (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Technology startups are constantly emerging, trying to create innovative solutions in environments of uncertainty, and because they face numerous challenges, they have high failure rates. The scarcity of resources and the product’s lack of adherence to market needs are among the challenges. In an attempt to alleviate these challenges, initiatives such as Continuous Experimentation arise. This approach supports systematical tests of hypotheses, helping teams prioritize deliveries that increase perceived value by the users. Our interview-based study aimed to identify how Continuous Experimentation is being adopted and how it underlies software engineering activities throughout the product development cycle of technology-based startups. We found that data-driven decisions and reduced development effort are benefits of adopting such an approach while the low competence and education in experimentation is among the main challenges, suggesting that there is room for qualifying professionals in the matter.